Comparison of inductively coupled plasma mass spectrometry and molybdenum blue colorimetry for total phosphorus determination in freshwater invertebrates - Molly S. Costanza-Robinson; Baker J. Angstman; Qiting Cai; Charles Forbes; Julia S. Keon; Shuyi Lin; Emma D. Neill; Elizabeth G. Peebles; Ella Roelofs; Eric K. Moody (PLoS ONE, 2025)
Molybdenum blue colorimetry (MBC) is the dominant, well-established method used for determining total P in environmental media, including in organismal tissues. However, other elemental methods for P determination are available, including inductively coupled plasma mass spectrometry (ICP-MS). Given the extensive literature using MBC to determine P in organismal samples, it is important to assess P analyses by ICP-MS and MBC to ensure that the two methods produce comparable data. In this work, we compared ICP-MS and MBC for total P determination in freshwater invertebrates, including the potential for analytical interferences, by applying both methods to three standard reference materials (SRMs) and 106 freshwater invertebrate samples. Average total P recoveries for SRMs were slightly higher for ICP-MS (99.8 ± 5.2%) than MBC (96.5 ± 5.4%), but both methods indicated good accuracy. Total P in invertebrates determined using the two methods was strongly linearly correlated (r = 0.96) with a slope of 1.01. On the whole, total P measured using ICP-MS exceeded that measured by MBC, but average pair-wise differences in %P were biologically negligible (0.044 ± 0.054). %P for SRMs and invertebrate samples run on ICP-MS in kinetic energy discrimination and standard modes compared favorably (e.g., SRM P recovery of 102% by both methods), indicating negligible influence of polyatomic ions on ICP-MS analysis. Similarly, analysis of P spike recoveries by ICP-MS (100.2 ± 3.4%) and MBC (107.0 ± 2.8%) were both considered acceptable. We conclude that ICP-MS represents a reliable and comparable alternative to MBC for determining total P in freshwater invertebrates while also offering the opportunity to measure additional biologically relevant elements in a single analysis.